Substructure in black hole scaling diagrams and implications for the coevolution of black holes and galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Davis, Benjamin L.; Sahu, Nandini; Graham, Alister W.
Abstract: Our multi-component photometric decomposition of the largest galaxy sample to date with dynamically-measured black hole masses nearly doubles the number of such galaxies. We have discovered substantially modified scaling relations between the black hole mass and the host galaxy properties, including the spheroid (bulge) stellar mass, the total galaxy stellar mass, and the central stellar velocity dispersion. These refinements partly arose because we were able to explore the scaling relations for various sub-populations of galaxies built by different physical processes, as traced by the presence of a disk, early-type versus late-type galaxies, or a Sérsic versus core-Sérsic spheroid light profile. The new relations appear fundamentally linked with the evolutionary paths followed by galaxies, and they have ramifications for simulations and formation theories involving both quenching and accretion.